Effects of dietary supplementation of palm fatty acid powders on performance, internal egg quality and yolk oxidation stability in laying hens during early egg production - JAHANIAN, R; RASOULI, E (The Indian Journal of Animal Sciences, 2014)
The present study was conducted with Hy-Line W-36 Leghorn hens to investigate the effects of dietary substitution of soybean oil (SO) with 2 commercial palm fatty acid powders (PFAP) on performance, egg quality measurements and oxidative stability of yolk lipids. Laying hens (225) were fed with a basal diet containing 3.5% soybean oil in which SO was replaced with PFAP (either energizer A or B) by 25, 50, 75 or 100%. Dietary treatments had no significant effect on egg production during 27 to 32 wk of age, but incremental levels of both PFAP sources reduced hen-day egg production during 32 to 37 wk of age. Energizer B was associated with more egg production and egg mass compared with energizer A. Dietary supplementation with PFAP increased feed intake compared with control group during 32 to 37 wk of age. Although feed conversion ratio (FCR) was not affected by experimental diets from 27 to 32 wk of age, the best FCR values assigned to the birds on control diet in the second 35 d, and birds on energizer B improved FCR compared with those on energizer A-diets. PFAP improved Haugh unit during both recording periods. All dietary replacement levels of PFAP were associated with higher standing-up quality of egg yolks. Diets supplemented with energizer B improved shell thickness and subsequently eggshell breaking strength compared with energizer A or control diets. Yolk cholesterol content was higher in eggs laid by hens fed on A- and B-containing diets compared with control birds. Dietary inclusion of PFAP partially or completely in place of SO reduced egg yolk malondialdehyde. The present findings suggested that one can replace 75% of SO with PFAP without any detrimental effect on performance and egg quality. In addition, yolk oxidative stability could be improved with PFAP.